2008
DOI: 10.1029/2008gl033172
|View full text |Cite
|
Sign up to set email alerts
|

Western Canadian glaciers advance in concert with climate change circa 4.2 ka

Abstract: [1] Disparate climate proxies from the Northern Hemisphere record a climate event at 4.2-3.8 ka. Here we show that glaciers throughout the mountain ranges of western Canada advanced at about this time. This conclusion is based on (1) new and previously reported radiocarbon ages on in situ stumps, logs, branches, and soils exposed by recent retreat in glacier forefields and (2) clastic-rich sediment intervals in cores retrieved from four montane lakes. These glacier and lacustrine data indicate a period of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…yr BP (Menounos et al, 2008;Ryder and Thomson, 1986). There is limited detrital and in situ evidence suggesting that glaciers may have repeatedly advanced into living forests in the southern Coast Mountains over this time (Koch et al, 2007b;Koehler and Smith, 2011;Mathews, 1951;Osborn et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…yr BP (Menounos et al, 2008;Ryder and Thomson, 1986). There is limited detrital and in situ evidence suggesting that glaciers may have repeatedly advanced into living forests in the southern Coast Mountains over this time (Koch et al, 2007b;Koehler and Smith, 2011;Mathews, 1951;Osborn et al, 2007).…”
Section: Introductionmentioning
confidence: 95%
“…Hence, there is no record of a substantial treeline drop around 2200 BC at MWA. The 2209 BC treeline decline at SHP corresponds temporally to the apparent 4.2-3.9 ka BP abrupt climate change event indicated in many widely distributed proxy records (Zhang and Hebda 2005;Booth et al 2006;Fischer et al 2008;Menounos et al 2008;Baker et al 2009). This ''event'' may have been a major contributing factor for massive old-world cultural change (Stanley et al 2003;An et al 2005;Staubwasser and Weiss 2006).…”
Section: Treeline Elevation and Temperature Inferencementioning
confidence: 99%
“…6.2-6.0 and 7.5-6.8 ka in the Canadian Rockies. Menounos et al (2008) identified a regional period of glacier advance across western North America ca. 4.2 ka based on glacial and lacustrine evidence.…”
Section: Regional Correlation and Discussionmentioning
confidence: 99%